Multidimensional poverty of children in Mozambique - Kristi Mahrt; Andrea Rossi; Vincenzo Salvucci; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
We analyse the multidimensional wellbeing of children aged 0-17 in Mozambique and find that 46.3 per cent can be considered multidimensionally poor. A substantial divide exists between urban and rural areas and between northern and southern provinces. We compare Mozambican children's wellbeing with that of children in other regional countries. Despite impressive gains in some indicators, multidimensional child poverty in Mozambique still substantially exceeds that in neighbouring countries. Targeted policies considering the specificities of child welfare are needed to ensure that the national-level growth and poverty reduction experienced by the population as a whole translate into better living conditions for children.
Keywords: I32; J13; 330; multidimensional poverty; children; child wellbeing; Mozambique